Sustainable low-cost carbon fibres produced by integrating wood fractionation with lignin fibre spinning - Yang,SM; Muazu,RI; Tran,E; Talbot,CB; Shah,N; Shaffer,MSP; Brandt-Talbot,A (RSC Sustainability, 2025)
Conventional carbon fibre manufacturing is costly and relies on fossil-based raw materials with significant environmental impacts. This study presents a new, low-cost route to biobased carbon fibres generated directly from wood by integrating ionosolv wood fractionation with carbon fibre spinning. The approach avoids isolating lignin powders by spinning lignin directly from the black liquor, offering a simpler process with a lower environmental impact. The concept is demonstrated using lignin extracted from eucalyptus wood into the recyclable ionic liquid (IL) N,N-dimethylbutylammonium hydrogen sulfate with 20% water, generating delignified cellulose pulp as a co-product. After adding non-toxic poly(vinyl alcohol) (PVA) into the lignin-containing ionic liquid (with up to a 4.7:1 lignin:PVA ratio) continuous lignin–PVA fibres were generated by spinning into an aqueous coagulation bath. Circular, homogenous fibres were formed, which were carbonised at 1000 °C, with carbon fibre yields of up to 37%. The proof-of-concept monofilament carbon fibres (452 MPa tensile strength and 43 GPa tensile modulus) outperformed carbon fibres generated from pre-isolated ionosolv eucalyptus lignin using the same fibre spinning approach. A techno-economic analysis (TEA) of the modelled process at scale suggests that carbon fibre production costs were $9.02 kg−1 for the integrated process and $9.69 kg−1 for the redissolution-spun carbon fibres, while life cycle assessment (LCA) indicated that 20.7 kg CO2-eq and 25.3 kg CO2-eq greenhouse gas emissions were associated with integrated and redissolution spinning, respectively, providing strong motivation for future optimisation of the carbon fibres' mechanical performance and for process development.